The Role of Gender in Language Acquisition: A Systematic Review of Recent Research - Evizariza Evizariza (Penelitian dan Pengembangan Ilmu, 2024)
This study addresses the relationship between gender stereotypes and language abilities in children, investigating how gender stereotypes influence language development in the early stages of life. The research background reflects the complexity of the interaction between social and cultural norms in influencing language use and understanding. The aim of this research is to understand the impact of gender stereotypes on children's language interest and performance, taking into account factors such as the influence of the social, cultural and family environment. The research methods involved an in-depth literature review covering a wide range of empirical studies on gender and language stereotypes in children. The results of the discussion show that gender stereotypes have a significant influence on children's interest, motivation and language performance. The implications of this research are the importance of awareness of gender stereotypes in the context of children's education and development, as well as the need for efforts to reduce the negative impact of gender stereotypes in language learning.